The Impact of Organizational Citizenship Behavior on Organizational Effectiveness - Sri Sunarsih, Endang; Kumala, Charisha Mahda (Economic and Business Horizon, 2024)
This study aims to analyze the role of Organizational Citizenship Behavior (OCB) in supporting organizational effectiveness and how workload affects this behavior in the work environment. OCB is voluntary behavior that is not included in the employee's formal duties but contributes to the performance of the organization. Meanwhile, workload refers to the number of tasks and work pressures that employees have to face in a given period. This study uses a quantitative approach with a survey method to collect data from employees in various organizations. The results show that OCB contributes positively to organizational effectiveness, while too high a workload can inhibit the emergence of this behavior. Therefore, organizations need to manage workloads proportionately to continue to support OCB behavior and improve employee well-being and productivity.